Um Deus, uma lei : as perspectivas políticas do imperador Justiniano a partir do Corpus Iuris Civilis - Mamedes, Kelly Cristina da Costa Bezerra de Menezes (2023)
The Roman Law can be considered one of the most notable and lasting contributions to Western civilization. A large part of the basic norms and institutions concerning the organization and regulation of socioeconomic life that are considered essential to guarantee what is called <rule of law= are the result of Roman legal thought. But most of what we know about him came from the compilation created during the rule of Emperor Justinian in the 6th century. The monarch governed the Eastern portion of the Roman Empire between the years 527-565 and among his plans to regain the greatness of the ancient Caesars was the production of a Codex that would preserve years of thought by the <iurisconsultos=. Therefore, it was their responsibility to correctly extract, amend and order all Roman legal production, trusting in God, who in the greatness of his goodness would be able to sanction and consummate achievements that would be totally beyond human will. The purpose of our work was to demonstrate that in addition to this speech, the legal compilation, called <Corpus Iuris Civilis=, was one of the most successful means of government propaganda used by Justinian, especially analyzing the laws that were promulgated by the emperor.